Spatial Analysis of Urban Centers in Taif Governorate Using Geographic Information Systems - Al-Enezi, Nada Suleiman Abdulaziz Al-Khalifi (Dirasat: Human and Social Sciences, 2025)
Objectives: the study aims to analyze spatial distribution pattern of urban districts in Taif Governorate, determine the extent of dispersion of urban centers from their general center, and recognize distributional trend of phenomenon of urban centers in Taif Governorate. the study also aimes to determine role of geographic information systems in the spatial analysis of urban centers in Taif in Saudi Arabia. Methods: descriptive approach was used to identify urban centers in Taif, and descriptive data associated with them, such as number of residents, dwellings, and other data related to reports for Taif. The study also adopted spatial statistical analysis through geographic information systems, which deals with revealing nature of distribution of urban centers and analyzing their patterns, using cartographic method, concerned with designing and producing maps specific to study area. Results: results of the study reveal that Taif city, according to weighted central phenomenon of population and number of dwellings, is considered center of spatial gravity in the governorate. The central circle included 8 urban centers, representing 80% of total number of centers. By applying the nearest neighbor coefficient, distribution pattern is an irregular dispersed pattern, and through Moran's analysis, distribution is a random pattern. Conclusion: Geographic Information Systems technology is important for recognizing reality of urban centers distribution in Taif Governorate, which has reached scientific results that benefit decision-makers and urban planners in determining reality of these centers, and nature of their spatial interactions to achieve sustainable urban development.